Analisis faktor yang mempengaruhi implementasi sistem informasi dan kinerja pegawai - Haryadi, Haryadi; Pratama, Reza Febriyan (Performance, 2018)
Purpose: This study aims to analyze the factors that affect the information system and employee performance of Bank bjb of Ciamis branch. Methodology: In this study, the determination of the sample is done by purposive judgment sampling technique that is all employees of Bank bjb of Ciamis branch involved in operational of Bank bjb of Ciamis branch. The number of research samples is 92 respondents. The analysis in this study used Partial Least Square (PLS). Findings: The results of this study indicate that there is significant effect of human resource and data quality on the implementation of information system. While, management support has no significant effect on the implementation of information system. Furthermore, human resource quality and management support have no significant effect on employee performance. While, data quality and the implementation of information system have significant effect on employee performance. Keywords: human resource quality, top management support, data quality, implementation of information system, performance.